Peran School Belonging dan Hardiness terhadap Motivasi Berprestasi pada Siswa Keluarga Menuju Sejahtera (KMS) - Geizy Azhari Putri; Fauzan Heru Santhoso (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Motivation is one of the important things for students in the learning process to accomplished the best achievement. This motivation for reaching the best achievement possessed by students provides enthusiasm, direction, and persistence in students’ behavior. As one of the psychological aspects, achievement motivation is influenced by individual factors, such as a sense of belonging to the school (school belonging) and hardiness. Regarding the achievement motivation of KMS students, the status of KMS students who are students from underprivileged families also contributes to individual achievement motivation, this is because families with low socioeconomic tend to prioritize how they survive rather than encouraging their children to excel. This research objective is to examine empirically the role of school belonging and hardiness in predicting motivation to reach the best achievement of KMS students. KMS students are students who come from families towards prosperity who receive educational assistance from the local government so that every underprivileged student can get a proper education. The research subjects were 226 KMS students from three Junior High Schools in the city of Yogyakarta. This research is non-experimental quantitative research with a survey method. The tools of measurement are used in scale of best performance motivation scale, psychological sense of school belonging and hardiness. The results of this study indicate that sense of school belonging and hardiness in collaboration are able to predict achievement motivation in KMS students. The relationship that occurs is positive, the higher school belonging and hardiness, the higher the achievement motivation of KMS students.